Migration, Transfers and Economic Decision Making among Agricultural Households: An Introduction - Davis, Benjamin; Carletto, Gero; Winters, Paul C. (2012)
The increasing volume of remittances and public transfers in rural areas of the developing world has raised hopes that these inflows may serve as an effective mechanism for reducing poverty in the long term by facilitating investments and raising productivity, particularly in agriculture where market failures are most manifest. The seven papers in this special issue systematically test the relationship between transfers and productive spending amongst rural households in six different countries. Overall, the studies embrace a less optimistic view of the role of migration and public and private transfers on agriculture, with migration as facilitating a transition away from agriculture or to models of less labour intensive agriculture.